Concerns for the agricultural resource basis with respect to bean production - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1988)
Agricultural development in Latin America and Africa is briefly analyzed, with particular reference to bean production. The major trends that affect bean production technology and its role in farming systems include population growth, especially in the highlands of Africa, and urbanization and income development in the agricultural sector, particularly in Latin America where more than 80 percent of the bean production (excluding seed production) is marketed. To maintain the agricultural resource basis, the genetic production base/region must be narrowed and appropriate measures taken to solve rising soil fertility problems (Africa), soil management problems (Latin America), and ecological and toxicological consequences of increased chemical control (Latin America). A sample questionnaire to determine environmental concerns (biological and physical), level of intervention (crop- system, farm, regional, global), and CIAT participation is annexed. (CIAT)